Understanding Islamic Banking Adoption among Non-Economics Students in Medan City: The Roles of Financial Literacy and Awareness - Elvina Zailanty Harahap; Nurul Inayah; Kamilah K. (FEBI IAIN Langsa, 2026)
This study aims to examine the influence of financial literacy and awareness on non-economics students' decisions to use Islamic banking services in Medan City. A quantitative survey approach was employed involving 96 respondents selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The findings reveal that financial literacy has no significant effect on the decision to use Islamic banking (β = 0.091; B = 0.093; t = 0.924; p = 0.358), whereas awareness has a positive and statistically significant effect (β = 0.512; B = 0.480; t = 5.169; p < 0.001) and emerges as the most influential predictor. Simultaneously, financial literacy and awareness significantly affect the decision to use Islamic banking (F = 21.579; p < 0.001), with an R² value of 0.317, indicating that the model explains 31.7% of the variance in respondents' decisions. Theoretically, this study contributes to the Islamic banking behavior literature by demonstrating that awareness is a stronger predictor than financial literacy among non-economics students. Practically, the findings suggest that strategies to increase Islamic banking adoption should not rely solely on financial education but should also emphasize awareness-building through socialization programs, digital media campaigns, and more effective communication strategies targeting university students.